The Human Gut Colonizer Blastocystis Respires Using Complex II and Alternative Oxidase to Buffer Transient Oxygen Fluctuations in the Gut - Tsaousis, Anastasios D.; Hamblin, Karleigh A.; Elliott, Catherine R.; Young, Luke; Rosell-Hidalgo, Alicia; Gourlay, Campbell W.; Moore, Anthony L.; van der Giezen, Mark (Frontiers in Cellular and Infection Microbiology, 2018)
Blastocystis is the most common eukaryotic microbe in the human gut. It is linked to irritable bowel syndrome (IBS), but its role in disease has been contested considering its widespread nature. This organism is well adapted to its anoxic niche and lacks typical eukaryotic features such as a cytochrome-driven mitochondrial electron transport. Although generally considered a strict or obligate anaerobe, its genome encodes an alternative oxidase. Alternative oxidases are energetically wasteful enzymes as they are non-protonmotive and energy is liberated in heat, but they are considered to be involved in oxidative stress protective mechanisms. Our results demonstrate that the Blastocystis cells themselves respire oxygen via this alternative oxidase thereby casting doubt on its strict anaerobic nature. Inhibition experiments using alternative oxidase and Complex II specific inhibitors clearly demonstrate their role in cellular respiration. We postulate that the alternative oxidase in Blastocystis is used to buffer transient oxygen fluctuations in the gut and that it likely is a common colonizer of the human gut and not causally involved in IBS. Additionally the alternative oxidase could act as a protective mechanism in a dysbiotic gut and thereby explain the absence of Blastocystis in established IBS environments.